2016
DOI: 10.1515/jvetres-2016-0051
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic characterisation and cytogenetic analysis of mesenchymal stem cells from equine bone marrow and foal umbilical cords during in vitro culture

Abstract: Introduction: The objective of the study was immunophenotypic and cytogenetic analysis of mesenchymal stem cells from equine bone marrow and foal umbilical cords during in vitro culture. Material and Methods: The mesenchymal stem cells were obtained from equine bone marrow of three horses and from foal umbilical cords of six foals. The cells were cultured in CO2 incubators by standard procedure. Quantitative abnormalities of chromosomes, i.e. aneuploidy and polyploidy, and structural aberrations, i.e. breaks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…However, BM-MSCs did not express N-Cadherin, another mesenchymal marker [18]. It can be speculated that BM-MSCs loose N-Cadherin expression during culture, since in another study regarding immunophenotypic characterization of equine BM-MSCs, it was observed that N-cadherin-positive cells were present at the second passage, whereas at the fifth passage these cells were not detected [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, BM-MSCs did not express N-Cadherin, another mesenchymal marker [18]. It can be speculated that BM-MSCs loose N-Cadherin expression during culture, since in another study regarding immunophenotypic characterization of equine BM-MSCs, it was observed that N-cadherin-positive cells were present at the second passage, whereas at the fifth passage these cells were not detected [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a comparable or even higher genetic stability was already shown with hPL compared to FBS ( 23 , 24 ). However, the genetic stability of equine MSC has so far only been studied with FBS ( 22 , 26 28 ). For this reason, in the present study, we analyzed the genetic stability of equine AD-MSC cultivated with either FBS or ePL.…”
Section: Introductionmentioning
confidence: 99%
“…Слід зазначити, що для лікування коня ми використовували стовбурові клітини третього пасажу, оскільки наші попередні дослідження показують, що рівень мінливості каріотипу мезенхімальних стовбурових клітин коней, зокрема, отриманих з кісткового мозку, на 3 пасажі культивування in vitro відповідає спонтанним рівням, характерним для цього виду тварин. Це свідчить про те, що ці клітини безпечні для терапевтичних цілей (Mazurkevych et al, 2016).…”
Section: матеріали і методиunclassified